Molecular diagnosis of Mycoplasma spp. Arthritis by PCR - Monzavi, Sakineh; Shahhosseiny, Mohammad Hassan; Taheri Sangsari, Gholamreza (Researcher Bulletin of Medical Sciences, 2019)
Background: Arthritis is one of the most common inflammatory diseases worldwide. It is characterized by symptoms such as systemic inflammation and autoantibody production. The molecular mechanisms in pathogenesis of arthritis are not fully understood. Studies show that many microorganisms, including Mycoplasmas, play a role in arthritis. The PCR method is a fast and accurate molecular method for the detection of Mycoplasma genus. The main objective of this study is the detection of Mycoplasma spp arthritis by PCR method. Methods: In this study, 70 samples of synovial fluid collected from Shariati hospital. DNA samples were extracted by phenol-chloroform standard method. Using several Mycoplasma standard strains and 16S rRNA gene target optimized PCR test of Mycoplasma spp. Sensitivity and specificity test were performed on the basis of standard methods and then performed on the DNA extracted of samples. Results: PCR product was amplified by 272 bp and was observed on 2% gel electrophoresis. Specificity test with DNA of other microorganisms showed 100% specificity of these primers. The limit of detection was evaluated 100 copy/reaction. From 70 samples of synovial fluid, 2 samples (3%) were positive and 68 cases (97%) were negative. Conclusion: This study showed that a number of infectious arthritis are Mycoplasma spp at the same time, and the PCR technique can be used as a sensitive and accurate way of early detection of Mycoplasma spp arthritis.